МЕТОДЫ ИССЛЕДОВАНИЯ ТОЛЕРАНТНОСТИ У СПЕЦИАЛИСТОВ СИСТЕМЫ ЗДРАВООХРАНЕНИЯ - Абидова, З.А. (SCIENCE and SOCIETY, 2016)
In the article there has been done the analysis of the existing research methods of tolerance in the scientific literature. The author offers a complex of diagnostic techniques to explore the level of tolerance with the specialists of the health system.